Defending Women Journalists in the Philippines from Threats and Intimidations - Gomez, Abigail C. (Future Science / FSH-PH Publications, 2023)
Despite the studies on defending journalism and coming up with various practices to protect journalists, still, the Philippines ranked as the third worst country in impunity versus journalists in the 2016 Global Impunity Index released by the Committee to Protect Journalists. In 2017, 2018, and 2019, it ranked fifth in the same impunity index. Then, the country ranked 7th and was still consistently part of the Top 10 rankings for the past three years, 2020, 2021, and 2022. This shows that the number of threats against journalists remains significant. This study deals with quantitative approaches to determine the threats and intimidations that selected women journalists face and provide course of actions which media companies may use to at least lower the ranking of the country in the impunity index. Results reveal that the most common threats and intimidations received by the women journalists in line of doing their duty are: blackmailing from sources, threats of physical violence, and public humiliation/ threats to humiliate (even in online platforms). Likewise, women journalists prove that they experience forms of harassments like receiving offers of sexual favors from their sources and employers in exchange of promotion and information privileges. To address these issues, corrective, preventive, and developmental actions are proposed to be implemented in respective media companies. Among these actions, the formation of a gender and development unit, ethics investigation committee, and local cybercrime division in the company are evaluated as the most acceptable and feasible actions for the women journalists. It is imperative that these recommendations be taken seriously and implemented to ensure a safer environment for women journalists in the Philippines and to safeguard the freedom and integrity of journalism in the country.